An advanced guide to psychological thinking : critical and historical perspectives - Ausch, Robert (Lexington Books, 2015)
An Advanced Guide to Psychological Thinking examines various areas of psychology including learning, neuropsychology, child development, and psychotherapy from a critical and historical perspective. It reveals how different conceptual tensions have created confusion in the discipline and helps psychology recognize its own foundations.